The Analysis of Pb and Cu levels in Canned fish and Sauces for the Storage Time - Hefinda Erfiandika; Asnawati Asnawati; Anak Agung Istri Ratnadewi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2014)
Lead (Pb) is pollutant that found in canned foods which derived from the soldering between the can and the lead. Copper (Cu) is one of material which one tin packaging can be oxidized and dissolved in acidic foods. Pb and Cu are not dangerous at lowest but it can cause botulism in gross. The storage time can affect the solubility of the metals. The purpose of the research is to know levels metal Pb and Cu in fishes and sauces canned and compared with limit BPOM. The limit of BPOM in canned fish for metal Pb is 0,3 ppm and for metal Cu is 5 ppm. The steps of the method are optimization the method of destruction and the measurement using Atomic Absorption Spectrofometry (SSA). The result shows that the storage time give effect to the greater of metal Pb and Cu in fish and sauce.The content of metal Pb in all sample exceeded the limit of BPOM. The content of metal Cu in sample A does not exceed in fish and sauce. The first month of sample B does not exceed, but the sixth month up to the twenty fourth month exceed the limit of BPOM in fish and sauce. The precision in all the measurement have on average <2 %, it shows that all the measurements are good repetition. Keywords: Lead , Copper, Atomic Absorption Spectrofometry, fish, Sauce